Pengaruh Gaya Hidup, Label Halal, dan Harga Terhadap Keputusan Pembelian Pada Produk Skincare MS GLOW (Studi Kasus Mahasiswa FEB UNISMA Angkatan 2019) - Lidya Ayu Ferdyana; Nurhajati Nurhajati; Muhammad Ridwan Basalamah (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to examine and explain the Influence of Lifestyle, Halal Labeling, and Prices on Purchase Decisions for MS GLOW Skincare Products in a case study of Students of the Faculty of Economics and Business, Islamic University of Malang, Class of 2019. This study uses a quantitative approach which uses the Slovin formula because the population has it is known, seeing from the results of calculating the Slovin formula to get the results of a total sample of 90 respondents. To solve the problem in this study using SPSS in analyzing, normality test, classic assumption test, hypothesis test, multiple linear regression test and adjusted R² coefficient test. The results of this study are Lifestyle, Halal Label, Prices simultaneously influence Purchasing Decisions. Keywords: Lifestyle, Halal Label, Price, Purchase Decision